Effects of multidisciplinary rounds and checklist in an Intensive Care Unit: a mixed methods study - Edilaine Maran; Laura Misue Matsuda; Alexandre Biasi Cavalcanti; Ana Maria Muller de Magalhães; Sonia Silva Marcon; Maria do Carmo Fernandez Lourenço Haddad; Alessandra Cristina Gobbi Matta; Maria Antonia Ramos Costa (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to analyze the implementation of multidisciplinary checklist-directed rounds before health indicators and multidisciplinary team perception of an Intensive Care Unit. Methods: a mixed methods study, with an explanatory sequential design, carried out at a hospital in southern Brazil, from September 2020 to August 2021. The integration of quantitative and qualitative data was combined by connection. Results: after the implementation of checklist-directed rounds, there was a significant reduction in hospital stay from ventilator-associated pneumonia, urinary tract infection and daily invasive device use. The investigated practice is essential for comprehensive care, harm reduction, effective work and critical patient safety. Conclusions: the multidisciplinary rounds with checklist use reduced data on health indicators of critically ill patients and was considered a vital practice in the intensive care setting.